Are postnatal ampicillin levels actually related to the duration of intrapartum antibiotic prophylaxis prior to delivery? A pharmacokinetic study in 120 neonates. Issue 2 (29th June 2017) - Berardi, Alberto; Pietrangiolillo, Zaira; Bacchi Reggiani, Maria Letizia; Bianco, Valentina; Gallesi, Daniela; Rossi, Katia; Facchinetti, Fabio; Ferrari, Fabrizio
Abstract : Objective: To assess ampicillin levels according to the duration of intrapartum antibiotic prophylaxis (IAP). Design: Prospective cohort single-centre study. Setting: Tertiary care centre (Modena, Italy). Patients: 120 neonates≥35 weeks' gestation exposed to IAP. Interventions: Neonates were divided into four groups, according to the duration of IAP prior to delivery: group 1 (n=30; <1 hour), group 2 (n=30; ≥1 and <2 hours), group 3 (n=30; ≥2 and <4 hours) and group 4 (n=30; ≥2 doses, ≥4 hours). Main outcome measures: Blood samples were collected at delivery (from the umbilical cord) and at age 4 hours (from a peripheral vessel). Results: Median duration of IAP was 121 min (range 7–2045 min). Median ampicillin levels in umbilical cord blood were 10.4 µg/mL (IQR 6.4–14.9) and in peripheral blood were 4.7 µg/mL (IQR 2.8–6.4µg/mL). Umbilical cord blood levels reached a peak approximately 30 min after IAP and then declined significantly (p<0.001). Peripheral blood levels did not differ among study groups. Neonates exposed to a full loading dose (n=115) had peripheral blood levels 2.5–70 times higher than the minimal inhibitory concentration for group B streptococcus. There was no relationship between neonatal ampicillin concentrations and the duration of IAP prior to delivery (β=−0.0003, 95% CI −0.02 to 0.001, p=0.680). Conclusions: Ampicillin levels reach a peak in the umbilical cord blood within 30 min of intrapartum administration. After a full loading dose, bactericidal levels persist for at least 4 hours after birth and seem independent of the duration of IAP prior to delivery.